Common lands are not wastelands - ElDidi, Hagar; Khurana, Ritika; Zhang, Wei; Jadav, Maheshkumar Kalidas; Guha, Chiranjit; Priyadarshini, Pratiti; Guo, Zhe; Sandhu, Harpinder; Nagendra, Harini; Meinzen-Dick, Ruth S. (India Water Portal, 2024)
What are common lands? What is the state of common lands in India?